2019
DOI: 10.2147/dmso.s205379
|View full text |Cite
|
Sign up to set email alerts
|

<p>Plausible relationship between homocysteine and obesity risk via <em>MTHFR</em> gene: a meta-analysis of 38,317 individuals implementing Mendelian randomization</p>

Abstract: Objective Numerous studies have explored the role of methylenetetrahydrofolate reductase gene ( MTHFR ) C677T polymorphism and homocysteine (Hcy) concentration in obesity, but the results are inconsistent. Hence, we performed a meta-analysis implementing Mendelian randomization approach to test the assumption that the increased Hcy concentration is plausibly related to the elevated risk of obesity. Methods Eligible studies were selected based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 61 publications
3
28
0
Order By: Relevance
“…BMI, as a proxy for general obesity, cannot distinguish lean mass and adipose tissue, which may also confuse the relationship between obesity and HCY. Although the mechanism was still unclear, these results suggest that the Hcy metabolic pathway may play an important role in obesity 25 . In addition, we found that Hcy level was negatively correlated with blood glucose and HDL, which is consistent with previous reports 41 that hyperhomocysteinemia (HHcy) was associated with low levels of HDL.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…BMI, as a proxy for general obesity, cannot distinguish lean mass and adipose tissue, which may also confuse the relationship between obesity and HCY. Although the mechanism was still unclear, these results suggest that the Hcy metabolic pathway may play an important role in obesity 25 . In addition, we found that Hcy level was negatively correlated with blood glucose and HDL, which is consistent with previous reports 41 that hyperhomocysteinemia (HHcy) was associated with low levels of HDL.…”
Section: Discussionmentioning
confidence: 90%
“…However, results on the relationship between BMI and Hcy levels showed conflicting data 24 . A recent meta-analysis reported that Hcy was positively correlated with obesity 25 , while a recent study demonstrated opposite results in the general population 26 . A recent cross-sectional study showed that Chinese bipolar disorder (BD) patients with hyperhomocystinemia had elevated BMI 16 .…”
Section: Introductionmentioning
confidence: 95%
“…Twin family and adoption studies indicates the heritability rate of BMI is high (i.e. ;40–70%) indicating as genetic factors have the pivotal role in pathophysiology of obesity ( Fu et al, 2019 ). Heritability in terms of parental obesity is found to be important risk factor for childhood and adolescent obesity ( Danielzik et al, 2002 ).…”
Section: Geneticsmentioning
confidence: 99%
“…Vegetables and fruits contain a wide range of constituents with potential impact on human health. However, the discussion focused exclusively on the potential role of vitamin C itself, with no mention of any of the other potentially beneficial constituents of vegetables and fruits, such as nitrate ( 3 ), phytochemicals ( 4 ), and folate ( 5 ). There is no mention of the possibility that the vitamin C intake/plasma concentration might be simply a marker of intake of vegetables and fruits, in which case vitamin C itself may have only a minor role in the association or, maybe, none at all.…”
Section: Introductionmentioning
confidence: 99%